-تأثير أزمة كورونا علىبقاء المؤسسات الصغيرة والمتوسطة في الجزائر-دراسة حالة - فخار محمد; فرحات أحميدة (جامعة عمار ثليجي الاغواط, 2021)
This study aims to identify the most important factors affecting the survival of small and medium enterprises in Algeria during the Corona crisis, we use “survival” as a synonym for success in our study, We conducted a field study of a sample of institutions in the states of Ghardaia and Algiers, using the interview to collect information, then we used the nvivo program to analyze the data as it is the most appropriate for such studies. The study brought us to the conclusion that the survival of small and medium enterprises in the midst of the Corona crisis depends on the amount of attention received by the functions of the institution, that is, the more the institution pays More production function (for industrial enterprises The catering function for service establishments (the greater the probability of their survival in the market as a basic function consisting of the sum of the other functions, and the impact ratio is as follows: To produce 241 iterations, then purchases 111 iterations, then marketing 110 iterations, then Storage 57 iterations then research and development 56 iterations then HR 54 iteration then Finance and Accounting 25 iterations.